Effect of Aluminum Doping on the Growth and Optical and Electrical Properties of ZnO Nanorods. Issue 5 (26th March 2014) - Chen, Ruiqiang; Zhu, Pengli; Deng, Libo; Zhao, Tao; Sun, Rong; Wong, Chingping
Abstract Aluminum‐doped zinc oxide (AZO) nanorods were successfully prepared by a convenient solvothermal route. The crystal structure and morphology of AZO were characterized by XRD, SEM, and high‐resolution TEM. The length and diameter of AZO nanorods decreased with increasing Al content. The optical and electrical properties of AZO were studied by UV/Vis spectroscopy and a four‐point probe. The optical band gap of AZO increased initially because of the Burstein–Moss effect and then decreased as the Al content increased owing to the defects of AZO. The electrical resistivity of AZO nanorods varied conversely because of the change of electron and defect concentration (native and impurity defects). The native defect types, which were singly charged zinc and oxygen vacancies, were confirmed by photoluminescence spectroscopy. Moreover, not only the properties but also the growth mechanisms of AZO nanorods were affected by the defect concentrations of singly charged zinc vacancies and substituted Al, which were caused by increasing Al content. Finally, the AZO exhibited the smallest electrical resistivity with 1.5 at. % Al doping content, which was four orders of magnitude smaller than that of ZnO.